RELATIONSHIP BETWEEN OFFICE DESIGN ON EMPLOYEE’S PRODUCTIVITY AT SAJ HOLDINGS SDN. BHD. - Nur Adilla Roslani; Siti Nurul Akma Ahmad; Nor Maslia Rasli Samudin; Nurhafizah Mohd Zolkapli; Siti Norashikin Bashirun (International Journal of Accounting, Finance and Business, 2021)
The productivity improvements have been recognized to have a major impact on economic growth and a higher standard of living on many economic and social phenomena. Companies must continuously improve their productivity to stay profitable. Therefore, this research aims to study the relationship between office design which focuses on lighting and noise on employee productivity. The study was conducted at SAJ Holdings Sdn. Bhd. which involved 140 respondents through simple random sampling. The researcher used the structured questionnaire from the previously published research as the measurement for this study. A set of questionnaires was distributed to the respondent and the data collected were analyzed using Statistical Package for Social Science (SPSS). The result obtained shows that there was a significant relationship between office design (noise and lighting) towards employee productivity. Also, the level of employee productivity at SAJ Holdings Sdn. Bhd. is above average. Thus, this study concluded that office design is a crucial factor that drives towards increasing employee productivity and the entire organization's success as well as in achieving business goals, vision, and mission.